PERAN BUDAYA ORGANISASI MEMODERASI PENGARUH KOMPETENSI PROFESIONAL DAN DISIPLIN KERJA TERHADAP KINERJA GURU (Studi Kasus Pada SMA Negeri di Kecamatan Pati Kabupaten Pati) - Sih Retno Marsanti, 12.52.02.0221; ., Sunarto (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research is intended to examine the influence of professional competence and discipline performance to teachersâ work performance with the moderation of organizational culture. The specific purpose of this research is to examine the role of organizational culture moderates the influence of professional competence and discipline performanceÂ  to the teachersâ work performance. The usage of this research is to explain and expand the previous researches about the role of organizational culture Â moderates the influence of professional competenceÂ  and discipline performanceÂ  to the teachersâ work performance. This research used the population of 166 teachers of state senior high school in Pati District, Pati Regency. The analysis technique used in this research is regression model moderate quasi. Based on the research result can be conducted that: professional competenceÂ  influences teachersâ work performance, discipline performanceÂ  influences the teachersâ work performance, organizational cultureÂ  Â strengthenÂ  the influence of professional competence to teachersâ work performance, organizational cultureÂ  strengthen the influence of discipline performanceÂ  to the teachersâ work performance.Keywords: Professional Competence, Discipline Performance, Organizational Culturecand Teachersâ Work Performance